2016
DOI: 10.1007/s00018-016-2235-9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal stem cell response to injury: lessons from Drosophila

Abstract: Many adult tissues and organs are maintained by resident stem cells that are activated in response to injury but the mechanisms that regulate stem cell activity during regeneration are still poorly understood. An emerging system to study such problem is the Drosophila adult midgut. Recent studies have identified both intrinsic factors and extrinsic niche signals that control the proliferation, self-renewal, and lineage differentiation of Drosophila adult intestinal stem cells (ISCs). These findings set up the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 96 publications
(206 reference statements)
3
113
0
1
Order By: Relevance
“…Alternatively, other nonapoptotic damage signals produced by infected villus cells may indirectly stimulate WNT secretion from other cell types (e.g., Paneth cells), leading to stem cell activation. Such feedback mechanisms from differentiated cells to stem cells are not well understood in mammalian systems, but several studies in the Drosophila gut have shown the importance of the JAK-STAT pathway (Beebe et al, 2010; Buchon et al, 2009; Jiang et al, 2016; Lin et al, 2010). Stress, injury, and bacterial infection can lead to cytokine production in damaged cells, stimulating the JAK-STAT pathway in WNT-producing cell types, which manifests into ultimate ISC proliferation (Jiang et al, 2016; Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, other nonapoptotic damage signals produced by infected villus cells may indirectly stimulate WNT secretion from other cell types (e.g., Paneth cells), leading to stem cell activation. Such feedback mechanisms from differentiated cells to stem cells are not well understood in mammalian systems, but several studies in the Drosophila gut have shown the importance of the JAK-STAT pathway (Beebe et al, 2010; Buchon et al, 2009; Jiang et al, 2016; Lin et al, 2010). Stress, injury, and bacterial infection can lead to cytokine production in damaged cells, stimulating the JAK-STAT pathway in WNT-producing cell types, which manifests into ultimate ISC proliferation (Jiang et al, 2016; Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such feedback mechanisms from differentiated cells to stem cells are not well understood in mammalian systems, but several studies in the Drosophila gut have shown the importance of the JAK-STAT pathway (Beebe et al, 2010; Buchon et al, 2009; Jiang et al, 2016; Lin et al, 2010). Stress, injury, and bacterial infection can lead to cytokine production in damaged cells, stimulating the JAK-STAT pathway in WNT-producing cell types, which manifests into ultimate ISC proliferation (Jiang et al, 2016; Xu et al, 2011). Our previous study observed a robust upregulation of the interferon pathways in the intestinal epithelium following RV infection in the human intestinal enteroids (Saxena et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As well as wing disc injury (Díaz‐García and Baonza, ), adult epithelial injury (Rämet et al, ) and embryonic dorsal closure (Noselli and Agnès, ) are also used to investigate wound closure, successfully providing cellular and genetic insights relevant to vertebrates (Juarez, ). The gut is used to study injury responses of intestinal stem cells, regulated by intrinsic signals, and extrinsic niche signals for self‐replication (Jiang et al, ). These findings strongly suggest that regeneration reactivates mechanisms for cell organization normally driving development.…”
Section: Drosophila Comes Of Age As a Model Organism To Investigate Rmentioning
confidence: 99%
“…Notably, local extrinsic feedback signals are critical within the fly intestine to regulate proliferation status of ISCs [reviewed in Jiang et al (2016)]. In theory, the ratio of EE cells within the tissue may be controlled via extrinsic feedback signals, intrinsic regulation, or a combination of both.…”
Section: Introductionmentioning
confidence: 99%